Behaviour and Failure of Steel Columns Subjected to Blast Loads: Numerical Study and Analytical Approach - Haitham Al-Thairy (Advances in Materials Science and Engineering)
The main objective of this study is the numerical simulation of the behaviour and failure patterns of steel columns under blast loads using the dynamic finite element package ABAQUS/Explicit. A numerical model is suggested and validated against published experimental tests on full-scale wide-flange steel columns subjected to dynamic blast loads under constant axial compressive force. Afterwards, the validated model is used to investigate the effect of important parameters on the behaviour and failure patterns of steel columns under blast pressure through an extensive parametric study. The parameters include the blast impulse, the blast energy, the blast load, the blast duration, the column boundary condition, the column slenderness ratio, and the blast direction. The conclusions extracted from this parametric study may be used to develop a thorough understanding of the behaviour and failure of steel columns subjected to blast load which, in turn, could lead to a more accurate practical design procedure. The study also presents derivations and validations of a proposed analytical approach to calculate the critical blast impulse at which a steel column losses its global stability. Comparison between the critical impulse-axial force curves obtained from the proposed equation and that extracted from numerical simulations indicates the validity and feasibility of the proposed equation.